2015
DOI: 10.1007/s00774-015-0675-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray absorptiometry, peripheral quantitative computed tomography, and micro-computed tomography techniques are discordant for bone density and geometry measurements in the guinea pig

Abstract: This study aims to examine agreement among bone mineral content (BMC) and density (BMD) estimates obtained using dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), and micro-computed tomography (μCT) against high-resolution μCT and bone ash of the guinea pig femur. Middle-aged (n = 40, 86 weeks) male guinea pigs underwent in vivo followed by ex vivo DXA (Hologic QDR 4500A) scanning for intact and excised femur BMC and areal density. To assess bone architecture and stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Notably, DXA failed to represent not only qualitative but also quantitative parameters (BV/TV) measured by micro-CT in the fracture group, resulting in overall imprecision of DXA measurements for these patients. Our findings are consistent with published cadaveric and animal studies, which have shown a significant difference or a lack of correlation between micro-CT and DXA for femoral, iliac, and mandibular bone samples 21,22 . This low correlation between micro-CT and DXA is not only of theoretical interest but also bears high clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, DXA failed to represent not only qualitative but also quantitative parameters (BV/TV) measured by micro-CT in the fracture group, resulting in overall imprecision of DXA measurements for these patients. Our findings are consistent with published cadaveric and animal studies, which have shown a significant difference or a lack of correlation between micro-CT and DXA for femoral, iliac, and mandibular bone samples 21,22 . This low correlation between micro-CT and DXA is not only of theoretical interest but also bears high clinical relevance.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with published cadaveric and animal studies, which have shown a significant difference or a lack of correlation between micro-CT and DXA for femoral, iliac, and mandibular bone samples. 21,22 This low correlation between micro-CT and DXA is not only of theoretical interest but also bears high clinical relevance. Several ex vivo studies have suggested higher validity for micro-CT than DXA for the prediction of mechanical bone properties.…”
Section: Diagnosticsmentioning
confidence: 99%